Educação de jovens e adultos no MST: a experiência de escolarização no Assentamento Eldorado dos Carajás II, Mossoró – RN - Freitas, Thazia Lidia Xavier de (Universidade Federal Rural do Semi-Árido, 2020)
The main theme of this study is youth and adult education in the MST. It investigates the experience of schooling experienced in the "Basic Education Project for the Construction of Full and Participatory Citizenship", in the Eldorado dos Carajás II, Mossoró – RN, between 2014 and 2016. As a general objective of the study, it highlights "reflect on the experience of schooling of young people and adults of the Basic Education Project for the Construction of Full and Participatory Citizenship, from the perspective of students, from the Eldorado dos Carajás II Settlement, Mossoró - RN". In relation to the specific objectives, the following are scored: a) "to understand how the students think about the experience of schooling in the Basic Education Project for the Construction of Full and Participatory Citizenship of the Eldorado dos Carajás II, Mossoró – RN Settlement"; and b) "describe the contributions of the EJA to the subjects of the field from the experience of schooling in the Eldorado dos Carajás II, Mossoró – RN, from the perspective of students". From the methodological point of view, we used the qualitative approach and the biographical (auto) method and life histories. With the narratives of schooling of two students who experienced the experience in the agenda, reflections were apprehended. As a technique for the construction of the data, we highlight the semi-structured interviews, which were conducted in September 2020, validating the pandemic condition caused by COVID 19. As a conclusion of the study, the following stand out: the two students, participants of the study, perceive the experience of schooling as an experience that provided learning and personal growth, since educational actions excelled in dialogue and validating, in the teaching processes, the social and cultural reality in which they live. They highlight the need for non-interruption, as occurred with the project of which they were part, of public educational policies for the education of young people and adults in the MST. In addition, they reinforce that an education anchored in local issues, that is, contextualized with the social scope of life of the subjects of the EJA and Campo Education enhances a critical and liberating education that, by the way, leads to human formation
Keywords: Educação de Jovens e adultos; Movimento dos Trabalhadores Rurais Sem Terra; Paulo Freire; Educação do campo; Youth and Adult Education; Landless Rural Workers Movement; Paulo Freire; Country Education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL